Un-framing The Queer Media Body: A Virtual Reality Experimentation - Jordan Fraser Emery (The Journal of Studies in Language, Culture and Society)
The article explores and discusses a creative, digital, and visual representation of the research through the "RADICANT 003" virtual reality experience. Grounded in visual methods and the arts sciences, the article outlines its overall structure and contextualizes it within the broader doctoral research that in/forms it. It introduces Guma Joana, the Brazilian artist at the centre of this phase of the project. The research draws from an ethno-graphic study in a neoliberal context of her Instagram profile and 360° recordings of her performances. The article details two digital mechanisms designed to engage users in questioning their relationship to these images within the virtual reality environment: one mechanism deconstructs Instagram posts, while the other immerses the user in 360° videos.